Plasma shaping and its impact on the pedestal of ASDEX Upgrade: edge stability and inter-ELM dynamics at varied triangularity. (13th February 2018) - Laggner, F.M.; Wolfrum, E.; Cavedon, M.; Dunne, M.G.; Birkenmeier, G.; Fischer, R.; Willensdorfer, M.; Aumayr, F.
Abstract: The plasma shape, in particular the triangularity ( δ ), impacts on the pedestal stability. A scan of δ including a variation of heating power ( P heat ) and gas puff was performed to study the behaviour of edge localised modes (ELMs) and the pre-ELM pedestal stability for different plasma shapes. Generally, at higher δ the pedestal top electron density ( n e ) is enhanced and the ELM repetition frequency ( f ELM ) is reduced. For all δ, the pedestal top n e is already fully established to its pre-ELM value during the initial recovery phase of the n e pedestal, which takes place immediately after the ELM crash. The lowering of the f ELM with increasing δ is related to longer pedestal recovery phases, especially the last pre-ELM phase with clamped pedestal gradients (after the recovery phases of the n e and electron temperature ( T e ) pedestal) is extended. In all investigated discharge intervals, the pre-ELM pedestal profiles are in agreement with peeling–ballooning (PB) theory. Over the investigated range of δ, two well-separated f ELM bands are observed in several discharge intervals. Their occurrence is linked to the inter-ELM pedestal stability. In both kinds of ELM cycles the pedestal evolves similarly, however, the 'fast' ELM cycle occurs before the global plasma stored energy ( W MHD ) increases, which then provides a stabilising effect on the pedestal, extending the inter-ELM period in the case of the 'slow' ELM cycle. At the end of a 'fast' ELM cycle the n e profile is radially shifted inwards relative to the n e profile at the end of a 'slow' ELM cycle, leading to a reduced pressure gradient. The appearance of two f ELM bands suggests that the pedestal becomes more likely PB unstable in certain phases of the inter-ELM evolution. Such a behaviour is possible because the evolution of the global plasma is not rigidly coupled to the evolution of the pedestal structure on the timescales of an ELM cycle.